Weight of the Human Thyroid Gland A Postmortem Study - Nurunnabi, ASM; Alim, A; Sabiha, M; Manowara, B; Monira, K; Shamim, A (Bangladesh Journal of Medical Science, 2010)
Context: A cross-sectional study was designed to find out the difference in weight of the thyroid gland of Bangladeshi people in relation to age and sex and to compare with previous local and foreign studies. Materials & Methods: The present study was performed on 60 post mortem human thyroid gland (39 of male and 21 of female) collected from unclaimed dead bodies which were in the morgue under examination in the Department of Forensic Medicine, Dhaka Medical College, Dhaka. The samples were divided into three age-groups including Group A (10-20 years), Group B (21-50 years) & Group C (>50 years) and the weight of the thyroid glands were measured and recorded. Results: The mean weight of the thyroid gland in male was 15.14 gm, 19.20 gm and 14.64 gm and in female was 16.02 gm, 19.03 gm and 14.67 gm in group A, B and C respectively. The mean weight of the thyroid gland was 15.48 gm in group A, 19.15 gm in group B and 14.65 gm in group C. There was no difference in mean weight of the thyroid gland between male and female. The difference in mean weight of the thyroid gland between group A & group B and group B & group C were found statistically significant. The weight of the gland was found to increase from early childhood and puberty up to 50 years of age and then decrease. Key words: Thyroid gland; Weight of thyroid gland. DOI: 10.3329/bjms.v9i1.5230 Bangladesh Journal of Medical Science Vol.09 No.1 Jan 2010 44-48